Implementasi Perdagangan Karbon di Indonesia Pasca Terbitnya POJK Nomor 14 Tahun 2023 Tentang Bursa Karbon - Ariyanti, Suci; Abadi, Suwarno; Taufiqurrahman, Taufiqurrahman (Law and Humanity, 2024)
POJK Number 14 of 2023 on Carbon Exchange is the Government's effort to create a carbon trading arrangement through a carbon exchange. Previously, the government issued two regulations related to carbon trading, namely Presidential Regulation Number 98 of 2021 and Minister of Environment and Forestry Regulation Number 21 of 2022. However, it turns out that these regulations still have weaknesses. This research is a normative legal research. The results show that after the enactment of POJK on Carbon Exchange, there are still weaknesses where the basis of paid-up capital as a carbon exchange organizer is exactly the same as the stock exchange rules listed in Article 3 POJK 3/2021. This provision is considered to make the carbon exchange exclusive. In addition, several rules in POJK 14/2023 such as the form of carbon trading is securities, so there will be delisting, even though carbon has no such thing as disappearing or delisting. In addition, Article 27 related to the terms and procedures of carbon exchange organizers must meet the principles of openness, access, and equal opportunity contradicts the definition of carbon as securities. This is because if the form of carbon exchange has become securities, then those who will enter will also be stock exchange players. Therefore, this regulation does not explain who can be involved in carbon trading other than the organizers. Individuals, cooperatives, communities, NGOs can be involved in carbon trading or not.